If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14.40 + 4.05p = 4.50(3 + p) 14.40 + 4.05p = (3 * 4.50 + p * 4.50) 14.40 + 4.05p = (13.5 + 4.50p) Solving 14.40 + 4.05p = 13.5 + 4.50p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4.50p' to each side of the equation. 14.40 + 4.05p + -4.50p = 13.5 + 4.50p + -4.50p Combine like terms: 4.05p + -4.50p = -0.45p 14.40 + -0.45p = 13.5 + 4.50p + -4.50p Combine like terms: 4.50p + -4.50p = 0.00 14.40 + -0.45p = 13.5 + 0.00 14.40 + -0.45p = 13.5 Add '-14.40' to each side of the equation. 14.40 + -14.40 + -0.45p = 13.5 + -14.40 Combine like terms: 14.40 + -14.40 = 0.00 0.00 + -0.45p = 13.5 + -14.40 -0.45p = 13.5 + -14.40 Combine like terms: 13.5 + -14.40 = -0.9 -0.45p = -0.9 Divide each side by '-0.45'. p = 2 Simplifying p = 2
| y=13x+404+46 | | 3(3x-6)=1-2x | | x+(x-10)+2(x-10)+6=100 | | 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) | | -5.99+23.105x=-587.72x-54.936 | | 36-yi=4x+3i | | (x+2)=-(x-3) | | 5y=11x+6 | | f(x)=2x+3x-1 | | x^2-4x=x(7+x) | | -(x+2)=-(x-3) | | 12m^2-17m-5= | | 15-4x+16=11 | | -6x+15=18x-7 | | 0=-r+6 | | 0=[r+6] | | -(3x+1)=-5 | | a^2-4a+1=0 | | 4X+3-5+2X=20-3X+12 | | x(3x-2)=12x^2-2x-1 |